The Intersection of Gender, Language, and Virtual Learning: Advancing Equality in Thailand’s Film Industry - Piayura, Orathai; Sangsarapun, Wanida (Journal of Ecohumanism, 2025)
This qualitative study examines gendered aspects of language skill development in the Thai film industry on the metaverse. Employing purposive and snowball sampling, professionals from diverse industry roles participated, adhering to ethical guidelines and laws. Findings indicate gender disparities in English proficiency, highlighting the need for inclusive language programs. Empowering women through enhanced language skills can mitigate career barriers. Policy recommendations stress gender-inclusive education initiatives. Stakeholders should integrate tailored support for male and female participants as well as establish necessary legal measures. Future research should explore the connections between gender, language skills, and equality. Longitudinal studies can provide valuable insights into how these factors interact over time. This study emphasizes the critical importance of English proficiency in promoting gender equality. It highlights the necessity of cooperation from the government as well as across the industry-wide collaboration to address gender disparities and ensure equal opportunities for all.